2008
DOI: 10.1016/j.resuscitation.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arrest cooling with delayed reperfusion yields higher survival than earlier normothermic resuscitation in a mouse model of cardiac arrest

Abstract: SummaryBackground-Therapeutic hypothermia (TH) represents an important method to attenuate postresuscitation injury after cardiac arrest. Laboratory investigations have suggested that induction of hypothermia before return of spontaneous circulation (ROSC) may confer the greatest benefit. We hypothesized that a short delay in resuscitation to induce hypothermia before ROSC, even at the expense of more prolonged ischemia, may yield both physiological and survival advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 27 publications
4
77
0
1
Order By: Relevance
“…Such rapid ROS generation during minutes of reoxygenation could disrupt microvascular integrity and interrupt blood flow (25,38,56) and is likely related to the microvascular dysfunction that appears within the heart minutes after resuscitation (17). In the present study, the substantial loss of HCMVEC barrier integrity after oxidant stress is also consistent with the microvascular dysfunction seen in critical organs such as the heart and brain within hours of resuscitation (1,8,55).…”
Section: Akt Is Critical For Restoration Of H 2 O 2 -Induced Barrier supporting
confidence: 75%
“…Such rapid ROS generation during minutes of reoxygenation could disrupt microvascular integrity and interrupt blood flow (25,38,56) and is likely related to the microvascular dysfunction that appears within the heart minutes after resuscitation (17). In the present study, the substantial loss of HCMVEC barrier integrity after oxidant stress is also consistent with the microvascular dysfunction seen in critical organs such as the heart and brain within hours of resuscitation (1,8,55).…”
Section: Akt Is Critical For Restoration Of H 2 O 2 -Induced Barrier supporting
confidence: 75%
“…The intravenous administration of potassium chloride was also shown to induce a very reproducible cardiac arrest in rodents [9,13,14]. It leads to a quasi-immediate cardiac arrest with asystole.…”
Section: Asystole Through Potassium Chloride Administrationmentioning
confidence: 97%
“…On the other hand, spontaneous heart rate is much higher in rodents than in large animals and humans as usual values average 260-450 or 500-600 beats per minute in awake rats and mice, respectively [7,8]. This directly impacts the required chest compression rate in those species as mice should undergo ≈400 compressions per min to be resuscitated [9][10][11][12][13][14]. Magnetic resonance imaging also showed that usual ejection fraction are higher in mice as compared to humans (75% vs 55%) [15].…”
Section: Cardiac Arrest In Rodentsmentioning
confidence: 99%
“…4,5 The optimal timing of therapeutic cooling remains unclear. Animal models have demonstrated that immediate and faster cooling yields improved outcomes, [6][7][8] but other studies have suggested that no benefit exists in short-term survival with rapid cooling, even when compared to normothermic postresuscitation care. 8 Observational human studies, although limited by their design, have also yielded conflicting results, with rapid cooling reported to be associated with improved, neutral, and negative effects on neurologic status and mortality.…”
Section: Ré Sumémentioning
confidence: 99%